patients experiment with functional appliances: comparison between TB and ITMA - منصور علي (Latakia University Journal -Medical Sciences Series, 2023)
Objectives: To compare patients’ experiences with the Invisalign Teen with Mandibular Advancement (ITMA) and Twin Block (TB) appliances, both initially and after several months of wear. Materials and Methods: 10 patients completed an anonymous survey after 2 months of wearing ITMA or TB. 5 patients treated with ITMA (3 boys, 2 girls) and 5 patients treated with TB (3 boys, 2 girls), were included. Results: More patients using the TB found their appliance to be visually intimidating as compared with patients using the ITMA (21.7% vs 8.9%). TB was more noticeable than the ITMA (69.6% vs25%). Appliance insertion was more difficult for TB patients (21.8% vs 4.44% for ITMA). After 2 months, there were more reports of tooth soreness and lip/cheek soreness in the ITMA group. More TB patients required extra appointments for breakage (50% vs 22.2% for ITMA). Speech, drooling, and jaw and lip/cheek soreness worsened initially for both groups but improved over time. There were no differences between the groups regarding visible facial changes, satisfaction with treatment experience, or time to acclimatize to the appliance. Conclusions: TB and ITMA patients shared similar experiences for most of the parameters measured, but there were significant differences between the groups regarding appliance wear and management, discomfort, and function